AI-Based Deepfake Voice Detection Using MFCC Features and Random Forest Classification (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The rapid proliferation of AI-generated audio poses a serious threat to digital forensics, voice-based authentication, and information integrity. This paper presents a deepfake voice detection system that combines Mel-Frequency Cepstral Coefficient (MFCC) feature extraction with a Random Forest ensemble classifier to distinguish real human speech from synthetically generated audio. The proposed system processes input audio files in WAV or MP3 format, extracts 40 MFCC coefficients as the feature representation, and classifies each sample as real or fake through a trained Random Forest model. The complete pipeline is deployed as a Flask-based web application, enabling browser-based access without requiring any specialist software.Experimental evaluation was conducted on a balanced binary dataset comprising 300 real voice recordings and 300 AI-generated voice samples (total: 600 samples), split 80/20 for training and testing. The system was evaluated against two baseline classifiers under identical feature conditions. Results demonstrate that the proposed Random Forest model achieves an accuracy of 92.7%, precision of 91.9%, recall of 93.5%, and an F1-score of 92.7%, indicating strong effectiveness for practical deepfake audio detection. These results represent a substantial improvement over the SVM baseline (accuracy: 76.4%) and Decision Tree baseline (accuracy: 81.2%).